2014
DOI: 10.1016/j.eats.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Identification of the Anterolateral Ligament of the Knee

Abstract: Intense interest has focused on the recent description of the anterolateral ligament of the knee. Advancing knowledge of its anatomy and function is leading to a realization of its importance in the rotatory control of the tibia in anterior cruciate ligament injuries. Reconstruction of this structure will increasingly become an important goal during anterior cruciate ligament reconstruction. However, preoperative assessment of this ligament is difficult. Clinical assessment of rotatory laxity has poor reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…SonneryCottet et al [24] demonstrated an arthroscopic technique for ALL visualization; however, they only managed to visualize the most proximal portion of the ligament. According to the anatomical and resonance parameters In this image, it is possible to observe the spreading of ligament fibers immediately before the meniscal insertion Surg Radiol Anat described, the ALL insertion in the meniscus region should correspond to the location with narrower meniscal width, as it could serve as a guide in a possible attempt at arthroscopic location of this structure [7,10].…”
Section: Discussionmentioning
confidence: 98%
“…SonneryCottet et al [24] demonstrated an arthroscopic technique for ALL visualization; however, they only managed to visualize the most proximal portion of the ligament. According to the anatomical and resonance parameters In this image, it is possible to observe the spreading of ligament fibers immediately before the meniscal insertion Surg Radiol Anat described, the ALL insertion in the meniscus region should correspond to the location with narrower meniscal width, as it could serve as a guide in a possible attempt at arthroscopic location of this structure [7,10].…”
Section: Discussionmentioning
confidence: 98%
“…One of these articles was a recent technical note describing the arthroscopic identification of the ALL in a single patient, 13 which was not found to be adequate for data extraction and systematic review. Another article was a letter to the editor describing the identification of the ALL on magnetic resonance imaging (MRI), 14 which had an inadequate description of methods and, thus, was excluded.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…We did observe a connection between the ALL and lateral meniscus, which was also seen by many other investigators. Under arthroscopy, Sonnery-Cottet [15] observed the ALL to connect with the lateral meniscus as it passed though the lateral meniscus. Our anatomical findings of the ALL are consistent with descriptions provided from previous research on the ALL.…”
Section: Discussionmentioning
confidence: 99%